Flavonoids in Ageratum conyzoides L. Exert Potent Antitumor Effects on Human Cervical Adenocarcinoma HeLa Cells In Vitro and In Vivo. (4th May 2020) - Lin, Zeyan; Lin, Yanyan; Shen, Jinxing; Jiang, Meijiao; Hou, Youming
Abstract : The Ageratum conyzoides L. ( A. conyzoides ) is commonly used as a traditional medicine, and its antitumor effects have also been studied. However, the functional roles of flavonoids in A. conyzoides in antitumor activities have not been clarified. The present study is aimed at investigating the biological effects of flavonoids in A. conyzoides on human cervical adenocarcinoma. Firstly, we detected that flavonoids in A. conyzoides significantly inhibited the proliferation, invasion, migration, and clonality of human cervical adenocarcinoma HeLa cells in vitro . Furthermore, we found that flavonoids in A. conyzoides induced significant S phase arrest and apoptosis and obviously decreased the intracellular reactive oxygen species (ROS) level in HeLa cells. Finally, we found that flavonoids in A. conyzoides significantly inhibited the HeLa xenograft tumor growth and epithelial-mesenchymal transition (EMT) in vivo . In conclusion, our results demonstrated the obvious antitumor effects of flavonoids in A. conyzoides on HeLa cells, suggesting that flavonoids in A. conyzoides could be provided as a novel therapeutic compound for human cervical adenocarcinoma.